Observation on the foundation of kinetic theory of gases. (1982) - Basu, U.; Dutta, M.
Abstract : This paper deals with the study of the mathematical foundation of the Kinetic theory of gases. The significance of the Boltzmann model for a system of particles treated by classical mechanics is briefly explained. An apparent, but inherent difficulty in this model is pointed out.